2009
DOI: 10.1093/ndt/gfp417
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, overhydration and cardiac biomarkers in haemodialysis patients: a longitudinal study

Abstract: In the present study, we find a significant relation between BIA-derived BC parameters and natriuretic peptide concentrations. This relationship was independent of the cardiac history of the patient and suggests that the natriuretic peptide levels are to some degree modifiable by changing a patient's fluid distribution. Moreover, cTnT, BNP, NT-proBNP and hsCRP were significantly related, showing a complex relation between overhydration, malnutrition, inflammation and cardiac biomarkers in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
94
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 38 publications
14
94
2
1
Order By: Relevance
“…An increase in BNP concentration over time in dialysis patients has been previously demonstrated for both NT-BNP-76 (7,14,15) and BNP-32 (16), although two other studies demonstrated no significant change in these markers (17,18). The concurrent measurement of both forms of BNP in three groups of patients allowed us to directly compare patients with CKD 3-4 and KTRs to dialysis patients.…”
Section: Discussionmentioning
confidence: 91%
“…An increase in BNP concentration over time in dialysis patients has been previously demonstrated for both NT-BNP-76 (7,14,15) and BNP-32 (16), although two other studies demonstrated no significant change in these markers (17,18). The concurrent measurement of both forms of BNP in three groups of patients allowed us to directly compare patients with CKD 3-4 and KTRs to dialysis patients.…”
Section: Discussionmentioning
confidence: 91%
“…contemporaneous volume assessment with pre-and postdialysis multifrequency bioimpedance. As with other reports, we found that NT-proBNP values were not normally distributed (2-7); therefore, we logarithmically transformed data to allow standard statistical analysis (12).…”
Section: Discussionmentioning
confidence: 94%
“…However, there has been debate as to whether NT-proBNP is a marker of volume overload (7,12) or a marker of left ventricular dysfunction (2,13), and also studies that have reported no association with changes in left ventricular mass index or volume status (14). We therefore audited NT-proBNP in a cohort of stable adult hemodialysis outpatients who had MAP, mean arterial blood pressure; CTR, cardiothoracic ratio on chest x-ray; LV, left ventricular; ECW/TBW, extracellular water to total body water ratio; ⌬ECF BSA , change in extracellular fluid volume corrected for body surface area; Pre, prehemodialysis; Post, posthemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 clearly indicates a BCM (and not FFM) depletion and a higher ratio of ECW to ICW in the DG, considering that 1) a high R is correlated to small amounts of FFM; 2) for the same body mass, a low Xc indicates a decrease in the amount of BCM; and 3) a decrease in PA may be due both to a worsening in the hydration of the FFM and a decrease in the amount of the BCM relative to the amount of the FFM. An increase in the ratio of ECW to ICW is expected as a result of the decrease in BCM, which, in turn, may be attributed to protein-energy malnutrition [41], fast weight loss [42], or catabolic stress [43], as well as to elevated adiposity levels [44][45][46]. It has been suggested that under these circumstances the assessment of BCM is especially important, because its depletion (as well as that of the SMM) may be masked by normal values of FFM [47], as was observed in our sample comparing DG with CG.…”
Section: Discussionmentioning
confidence: 99%